WHAT HAPPENS AFTER THEY LAUGH: HOW HUMOROUS ADVERTISEMENTS HAVE AN EFFECT ON CONSUMERS’ ATTITUDES, WORD OF MOUTH INTENTIONS, AND PURCHASE INTENTIONS, WITH THE NEED FOR HUMOR PLAYING A MODERATING ROLE - Alfian Budi Primanto; Basu Swastha Dharmmesta (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction/Main Objectives: Even thought there is a risk from using humor as an advertising campaign strategy in industries which rely on trust and their technological prowess, like the telecommunications sector, the fact that there are a great number of humorous advertisements arranged by telecommunications companies in Indonesia needs to be researched. Background Problems: This research aims to narrow the phenomenon by investigating the effect of humorous advertisements with the need for humor as a moderating role on consumers’ attitudes, consumers’ intent to purchase, and their word of mouth intention. Novelty: By adding the need for humor in a moderating role, and the word of mouth intention as an endogenous variable, this research aims to extend the existing models of humorous advertising’s effectiveness. Research Methods: The research was designed to focus on consumers who can be classified as young adults (18 to 34 years old) and are not users of the mobile SIM card brands that the ad they perceived as funny ones. The researcher conducted a survey with a five point Likert scale, an online questionnaire, and purposive sampling as the primary data collection methods. Finding/Results: The result shows that although a humorous advertisement has a significant impact on the attitude toward the advertisement and the word of mouth intention, the humorous advertisement has no significant impact on the attitude toward the brand and the consumers’ intent to purchase. The need for humor failed to moderate the relationship between the humorous advertisement and the attitude toward the advertisement in this study. Conclusion: The researcher concludes that the impact of a humorous advertisement was limited to only entertaining the consumers, and to encourage their word of mouth intention, not their purchase intention.